ANALISIS POTENSI DAN PREFERENSI MASYARAKAT KELURAHAN SENGETI KABUPATEN MUARO JAMBI TERHADAP KEHADIRAN BANK SYARIAH - Erwin Saputra Siregar; Menik Anjarwasih; Arsa Arsa (Jurnal Ekonomi Rabbani, 2021)
This research aims to analyze the potential and preferences of the people of Sengeti Village towards Islamic banks. Potential is projected by demographics and the economy, while preferences are projected by people's perceptions, motivations, knowledge, and attitudes. The subject of this study is the community in Sengeti Village, while the object is the potential and preferences of the community. The population was all adults, and the authors took samples from populations aged 22 to 65 and obtained informants as many as 100 people. This study showed that potential and demographic variables corresponded to people's interest in using Islamic banks. In contrast, the preference variables demonstrated from the data showed that the community positively supported the existence of Islamic banks in Sengeti Village.